2016
DOI: 10.1515/sjs-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

How Do Second-Generation Immigrant Students Access Higher Education? The Importance of Vocational Routes to Higher Education in Switzerland, France, and Germany

Abstract: We analyse the access to different institutional pathways to higher education for second-generation students, focusing on youths that hold a higher-education entrance certificate. The alternative vocational pathway appears to compensate to some degree, compared to the traditional academic one, for North-African and Southern-European youths in France, those from Turkey in Germany, and to a lesser degree those from Portugal, Turkey, Ex-Yugoslavia, Albania/Kosovo in Switzerland. This is not the case in Switzerlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
12
0
3
Order By: Relevance
“…It also allows for cross-national comparative studies with datasets of other countries that have done the same (for examples of comparative analyses, see Picot & Hou, 2013;Murdoch et al 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also allows for cross-national comparative studies with datasets of other countries that have done the same (for examples of comparative analyses, see Picot & Hou, 2013;Murdoch et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, international comparative research could be further developed to study the impact of economic, institutional or social policy as well as other contexts on individual life courses (see, e.g. Buchmann, Kriesi, Koomen, Imdorf & Basler, 2016;Imdorf, Helbling & Inui, forthcoming;Imdorf & Hupka-Brunner, 2015;Kamanzi, Guégnard, Imdorf, Koomen & Murdoch, 2014;Murdoch, Guégnard, Griga, Koomen & Imdorf, 2016;Murdoch et al, 2017;Picot & Hou, 2013). To date, around 270 researchers and students from national and international institutions across a multitude of disciplines have been working with the TREE1 data.…”
Section: Data Usementioning
confidence: 99%
“…In Switzerland, students who follow a vocational track in secondary 2 education can obtain a Federal Vocational Baccalaureate which then gives access to universities of applied science. Research has shown that it is an important pathway to tertiary education, especially for students with a migrant background (for Albanian/Kosovan, former Yugoslavs, Portuguese and Turks in particular) (Murdoch et al, 2016). It would therefore be relevant to examine how the modes of grouping in secondary 1 education influence the orientation towards a vocational track.…”
Section: Discussionmentioning
confidence: 99%
“…Des recherches sur l'accès à la formation supérieure (Murdoch, Guégnard, Griga, Koomen & Imdorf, 2016 ;Murdoch, Guégnard, Koomen, Imdorf & Hupka-Brunner, 2014) ont montré notamment que les jeunes migrants de deuxième génération développaient avant tout des stratégies d'accès à la formation tertiaire distinctes de celles des jeunes Suisses. Pour eux, l'enseignement est plus souvent le produit d'une réorientation professionnelle, souvent la conséquence d'une première expérience d'insertion insatisfaisante sur un marché de l'emploi plutôt discriminant, notamment pour les femmes qualifiées (Riaño & Baghdadi, 2007).…”
Section: Un Marché De L'emploi Qui Résiste Aux Diplômés De Nationalit...unclassified